Endobronchial ultrasonography using a guide sheath technique for diagnosis of peripheral pulmonary lesions - Zhang, Lei (Endosc Ultrasound, 2017)
Endobronchial ultrasonography using a guide sheath (EBUS-GS) is a novel method used for collecting peripheral pulmonary lesion (PPL) samples. EBUS-GS is performed by introducing a guide sheath-covered miniprobe into the target bronchus and then withdrawing the miniprobe after lesion detection, leaving the guide sheath in situ as a working channel for obtaining lesion samples. EBUS-GS can improve PPL diagnosis rates and be used for obtaining specimens for molecular analysis. In this review, we discuss the clinical applications of EBUS-GS, the factors that affect its diagnostic sensitivity, and potential complications. We also compare EBUS-GS with other available diagnostic techniques and discuss the strengths and limitations of this method.